Spherical C-coated MnO composite material and preparation method and application thereof

By modifying the separator with spherical C@MnO composite material, the problems of polysulfide shuttle effect and slow reaction kinetics in lithium-sulfur batteries are solved, and the performance and service life of lithium-sulfur batteries are improved, which significantly improves the electrochemical performance.

CN119140088APending Publication Date: 2024-12-17NANJING UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411293609.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Due to the shuttle effect of polysulfides and slow reaction kinetics in lithium-sulfur batteries, the battery capacity is attenuated. Traditional separators cannot effectively inhibit the diffusion and catalytic conversion of intermediate products, affecting electrochemical performance.

Method used

Spherical C@MnO composite material is used as the diaphragm modification material, and through the composite of carbon and transition metal oxides, a uniform core-shell structure catalyst is formed, which enhances the catalytic conversion and physical limitation of polysulfides, improves lithium ion deposition uniformity and material stability. sex.

Benefits of technology

It significantly improves the electrochemical cycling and rate performance of lithium-sulfur batteries, extends the service life of the battery, and improves the conversion rate and electrochemical stability of polysulfides through catalytic action.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140088A_ABST
    Figure CN119140088A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite materials, and particularly relates to a spherical C-coated MnO composite material and a preparation method and application thereof. The invention synthesizes a transition metal oxide and carbon composite material (C (at) MnO core-shell structure catalyst with uniform size. The transition metal oxide prepared by the invention enhances the catalytic conversion of polysulfide, the uniform spherical structure has a physical limiting effect on the polysulfide and is beneficial to inducing uniform deposition of lithium ions, and the internal C material can stabilize the material structure in long circulation and prolong the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and particularly relates to a spherical C@MnO composite material and a preparation method thereof. Background Art

[0002] Among many emerging battery systems, lithium-sulfur batteries have the advantages of high theoretical energy density and specific capacity, low environmental pollution, abundant sulfur reserves and low price, and are regarded as very competitive next-generation secondary batteries. However, the development of lithium-sulfur batteries also faces many challenges, which seriously affect their commercialization process. Their electrochemical processes are plagued by slow sulfur reaction kinetics and the shuttle effect of lithium polysulfide. The shuttle effect caused by the diffusion of soluble lithium polysulfide and the slow electrochemical reaction caused by the low conductivity of sulfur and its reaction products are the main reasons for the capacity decay of lithium-sulfur batteries (Energy Storage Materials, 2019, 23, 707-732). To this end, people have carried out a lot of research, proposed a variety of coping strategies, and made a lot of progress.

[0003] The structure and performance of the separator greatly affect the electrode reaction of lithium-sulfur batteries and the shuttling of lithium polysulfide between the two electrodes. Currently, the most commercialized and widely used are polyolefin separators such as polyethylene (PE) and polypropylene (PP), which have the advantages of low cost, moderate mechanical strength and good chemical stability.

[0004] However, these traditional diaphragms have some disadvantages that cannot be ignored, such as the lack of polar groups, the inability to selectively inhibit the diffusion of intermediate polysulfides, and the relatively fixed pore size. Therefore, functional modification of commercial diaphragms to improve the ability to capture and catalyze polysulfides is of great significance to improving the electrochemical performance of lithium-sulfur batteries. In particular, by coating and modifying commercial diaphragms in a relatively simple process, giving them the functions of physical blocking, chemical adsorption, and catalytic conversion of polysulfides, it can effectively inhibit the shuttle effect of polysulfides and improve the electrochemical performance of lithium-sulfur batteries. Generally, a common method is to modify the diaphragm with a nanocarbon material coating. The nanocarbon coating has excellent conductivity and a complex pore structure, which can be used to adsorb polysulfides dissolved in the electrolyte and effectively inhibit the diffusion of lithium polysulfide through the diaphragm to the negative electrode, thereby significantly improving the rate performance and cycle performance of the battery. However, long-term cycling often easily leads to a decrease in the physical and chemical adsorption force between non-polar carbon materials and polar polysulfides, making it difficult to maintain a fixed connection, making it difficult to effectively anchor polar polysulfides during long-term cycling. Summary of the invention

[0005] In view of this, the present invention discloses a spherical C@MnO composite material and a preparation method thereof, which can effectively solve the problems of the shuttle effect caused by long-chain polysulfides and the slow reaction kinetics between polysulfide conversions.

[0006] It should be noted that current research has found that metal oxides (such as TiO, MnO, etc.), sulfides (such as CoS, CoS2, MoS2, etc.) and nitrides (such as TiN) have excellent catalytic ability and can promote the conversion of high-order polysulfides to low-order polysulfides (Advanced Energy Materials, 2019, 10, 1903008). Among them, transition metal oxides have significant advantages such as strong adsorption capacity to inhibit the polysulfide shuttle effect, good chemical stability to ensure long-term operation, catalytic effect to increase the redox conversion rate, and improve electrochemical cycle performance. It can provide strong support for improving the performance and application prospects of lithium-sulfur batteries. By combining carbon materials and transition metal oxides for the modification of diaphragms of lithium-sulfur batteries, the overall performance can be improved.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The first technical purpose of the present invention is to provide a spherical C@MnO composite material, which is a composite material (C@MnO) of transition metal oxide and carbon with uniform size and a core-shell structure catalyst.

[0009] The second object of the present invention is to provide a method for preparing the spherical C@MnO composite material as described above.

[0010] In order to achieve the above object, the present invention adopts the following technical solution:

[0011] A method for preparing a spherical C@MnO composite material comprises the following steps:

[0012] (1) mixing aqueous ammonia and anhydrous ethanol to obtain solution A; dissolving resorcinol in ultrapure water to obtain solution B;

[0013] (2) adding the solution A to the solution B, then adding a formaldehyde solution to react, centrifuging and washing the product to obtain a RF (resorcinol formaldehyde) spherical material;

[0014] (3) reacting the RF spherical material obtained in step (2) with a potassium permanganate solution, centrifuging and washing the product to obtain a RF@MnO composite material;

[0015] (4) The RF@MnO composite material obtained in step (3) is subjected to high-temperature heat treatment in an argon atmosphere to obtain a spherical C@MnO composite material.

[0016] Preferably, in step (1), the concentration of aqueous ammonia is 25%wt., the mixing ratio of aqueous ammonia to anhydrous ethanol is 1:10, and the stirring time is not less than 10 min; the concentration of resorcinol dissolved in ultrapure water is 0.3-0.4 M, and the stirring time is not less than 10 min.

[0017] Preferably, in step (2), the concentration of the formaldehyde solution is 30%-40% wt., the volume ratio of the formaldehyde solution to solution A and solution B is 1 mL:77 mL:10 mL; the reaction time for synthesizing the RF spherical material is 12-14 h, and the reaction temperature is 25-30° C.

[0018] Preferably, in step (3), the concentration of potassium permanganate solution is 0.05-0.08 M, the amount ratio of RF spherical material to potassium permanganate solution is 100 mg:10 mL, the reaction time is 6 h, and the reaction temperature is 25-30°C.

[0019] Preferably, in step (4), the temperature of the high temperature heat treatment is 400-600°C, the heating rate is 2-5°C / min, and the heat treatment time is 6-8h.

[0020] The third technical purpose of the present invention is to provide an application of the spherical C@MnO composite material as described above in the modification of the separator of a lithium-sulfur battery.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention synthesizes a transition metal oxide and carbon composite material (C@MnO) core-shell structure catalyst with uniform size.

[0023] (2) The transition metal oxide prepared by the present invention enhances the catalytic conversion of polysulfides. The uniform spherical structure has a physical restriction effect on polysulfides and is conducive to inducing uniform deposition of lithium ions. The internal C material can stabilize the material structure and extend the service life in a long cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0025] Figure 1 This is the X-ray photoelectron spectroscopy (XPS) graph of the C@MnO material prepared in Example 1.

[0026] Figure 2 These are the scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the C@MnO material prepared in Example 1.

[0027] Figure 3 The cross-sectional scanning electron microscope (SEM) image and macroscopic image of the C@MnO-PP prepared in the application example.

[0028] Figure 4 The diagrams show the adsorption experiment results and symmetrical battery tests performed in Example 1 and Comparative Example 1.

[0029] Figure 5 This is the C@MnO-PP prepared in the application example, the rate performance of the lithium-sulfur battery assembled with C-PP at 0.2C-4C, and the charge and discharge curve (GCD) at 0.5C.

[0030] Figure 6 This is the charge and discharge curve of the C@MnO-PP prepared in the application example and the lithium-sulfur battery assembled with C-PP at a charge and discharge rate of 0.5C.

[0031] Figure 7 This is a scanning electron microscope (SEM) image of the inhomogeneous RF material prepared in Comparative Example 2. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0034] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0035] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0036] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0037] The invention discloses a preparation method of a spherical C@MnO composite material and application of the spherical C@MnO composite material in modification of a diaphragm of a lithium-sulfur battery.

[0038] It should be noted that the experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are all commercially available unless otherwise specified.

[0039] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0040] Example 1: Preparation of C@MnO composite material

[0041] (1) Ammonia water (7 mL) was added to 70 mL of ethanol and marked as solution A, and stirred for 15 min. Resorcinol (0.04 mol) was dissolved in 10 mL of deionized water and marked as solution B, and stirred for 15 min. Formaldehyde solution (1 mL, 35% wt.) was added dropwise to the mixed solution and reacted at 25°C for 12 h. RF spheres were collected by centrifugation, deionized water and ethanol washing for multiple times.

[0042] If the ratio of solution A to solution B (77:10) is changed, the size and uniformity of the synthesized RF spheres will be affected, which is manifested in an increase in diameter and the appearance of a mixture of large and small spheres.

[0043] (2) 300 mg of RF spheres were mixed with 30 mL of KMnO4 solution (0.05 M), stirred for 6 h, and collected by centrifugation, deionized water, and ethanol washing multiple times to obtain the RF@MnO sphere composite material.

[0044] If the volume and concentration of KMnO4 solution are changed, or the reaction time is changed, the thickness of the MnO layer will be affected: the higher the concentration and the longer the reaction time, the thicker the coating will be, and vice versa. If the coating is too thick or too thin, it will affect the material properties: too thin will easily cause the shell to break during subsequent processing, making it difficult to maintain the original core-shell structure; too thick will reduce the reaction speed and increase the material density.

[0045] (3) 300 mg of the RF@MnO ball composite material was placed in a crucible, then heated to 600 °C in a tube furnace at 2 °C / min and calcined in an Ar atmosphere for 6 h to obtain the C@MnO ball composite material.

[0046] Figure 1 The XPS spectrum of C@MnO shows the generation of the material component C@MnO. Figure 2 a It can be seen that C@MnO was successfully synthesized, and the material retained the complete and uniform spherical structure of the original RF ball, while the rough surface was the embodiment of the coated MnO material. Figure 2 b There is a clear and thin envelope, which is the core-shell structure of C@MnO, with a MnO layer on the outside and a carbon core on the inside.

[0047] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples, test examples, and application examples are used to further illustrate the technical features disclosed in the present invention, but they should not be understood as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without creative work are also considered to fall within the scope of protection of the present invention.

[0048] Comparative Example 1: Preparation of Material C

[0049] (1) Synthesize RF spheres according to step (1) in Example 1.

[0050] (2) 300 mg of the RF ball composite material was placed in a crucible, then heated to 600 °C in a tube furnace and calcined in an Ar atmosphere for 6 h to obtain C material.

[0051] Comparative Example 2: Preparation of RF Balls with Changed Solution Mixing Ratio

[0052] Ammonia water (7 mL) was added to 40 mL of ethanol and marked as solution A, and stirred for 15 min. Resorcinol (0.04 mol) was dissolved in 40 mL of deionized water and marked as solution B, and stirred for 15 min. Formaldehyde solution (1 mL, 35% wt.) was dropped into the mixed solution, reacted at 25°C for 12 h, and RF spheres were collected by centrifugation, deionized water and ethanol washing multiple times.

[0053] Figure 7This is the SEM image of the RF sphere. It can be seen that the spherical material synthesized at this ratio has a very uneven size distribution.

[0054] Test example

[0055] The material must have excellent anchoring properties to quickly achieve effective modification of polysulfides, thereby producing good kinetic effects. The present invention uses a systematic approach to explore the adsorption characteristics of the prepared material on Li2S6, and evaluates the performance of the materials in Example 1 and Comparative Example 1 through adsorption experiments.

[0056] The specific operation steps are as follows: Li2S and S are dispersed in a mixed solution of ethylene glycol dimethyl ether (DME) at a molar ratio of 1:5, and a Li2S6 solution is obtained after vigorous stirring at 60°C for 48 hours. Equal masses of the two materials are weighed and added to the Li2S6 solution for standing, and the color change of the solution in the glove box is observed. The adsorption experimental effect is as follows: Figure 4 As shown in a.

[0057] Symmetric experiment: Li2S6 solution (0.2 mol L -1 ): Li2S and S (molar ratio of 1:5) were dissolved in a solution containing lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) (0.5 mol L -1 A symmetric cell was assembled using two identical electrodes and 20 μL Li2S6 solution.

[0058] The adsorption capacity of the target material for Li2S6 was evaluated by static adsorption experiments and UV-Vis spectroscopy (UV-Vis) analysis. The experimental results showed that the decolorization effect of the C@MnO-Li2S6 solution after adsorption treatment was low, indicating that the adsorption capacity of C@MnO for Li2S6 was effectively enhanced. In addition, further electrochemical test results showed that at 6mV s -1 Compared with the C material in Comparative Example 1, C@MnO can show a higher current response, indicating that it has excellent affinity and catalytic activity for LiPSs (see Figure 4 b), through comparison, the application performance research of C@MnO composite materials in lithium-sulfur batteries was improved.

[0059] Application example: C@MnO-PP (C-PP) diaphragm preparation

[0060] The C@MnO material conductive agent (Super P) and binder (PVDF) obtained in Example 1 were mixed and ground in a ratio of 8:1:1 for 30 minutes, and then N-methylpyrrolidone (NMP) solution was added and continued to grind to form a uniform slurry, and then the slurry was scraped on a commercial PP diaphragm and dried in an oven at 40°C for 10 hours to obtain a modified C@MnO-PP diaphragm. The C material obtained in Comparative Example 1 was used to replace the C@MnO material in the above steps, and a C-PP diaphragm was obtained by the same steps.

[0061] From the SEM image of the C@MnO-PP separator, it can be seen that the coating thickness is about 13 mm, as shown in Figure 3a. Figure 3 As shown in b, the modified membrane has good flexibility and good material adhesion, and the modified membrane will not fall off or be damaged due to bending.

[0062] C@MnO-PP (C-PP) is applied in Li-S batteries.

[0063] The obtained modified membrane was assembled into button batteries with sulfur / porous carbon positive electrode and metal lithium negative electrode respectively. 25 μL of electrolyte was dripped on both sides of the positive and negative electrodes to obtain lithium-sulfur batteries assembled with C@MnO-PP membrane and lithium-sulfur batteries assembled with C-PP membrane. Electrochemical tests were carried out after standing for 8 hours.

[0064] Figure 5 and Figure 6 The performance of different button cells assembled at 0.2-4C charge and discharge rates and the electrochemical data of 200 cycles at 0.5C rate are shown. The functional separator coated with the composite material effectively improves the electrochemical performance of the lithium-sulfur battery. The comparison shows that C@MnO has a significant catalytic effect on the conversion of polysulfides in lithium-sulfur batteries, thereby improving the life of lithium-sulfur batteries.

[0065] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A spherical C@MnO composite material, characterized in that: The spherical C@MnO composite material is a composite material (C@MnO) of transition metal oxide and carbon with uniform size and a core-shell structure catalyst.

2. A method for preparing the spherical C@MnO composite material as claimed in claim 1, characterized in that: The method specifically comprises the following steps: (1) mixing ammonia water and anhydrous ethanol to obtain solution A; dissolving resorcinol in ultrapure water to obtain solution B; (2) adding the solution A to the solution B, then adding a formaldehyde solution to react, centrifuging and washing the product to obtain a RF (resorcinol formaldehyde) spherical material; (3) reacting the RF spherical material obtained in step (2) with a potassium permanganate solution, centrifuging and washing the product to obtain a RF@MnO composite material; (4) The RF@MnO composite material obtained in step (3) is subjected to high-temperature heat treatment in an argon atmosphere to obtain a spherical C@MnO composite material.

3. The method for preparing the spherical C@MnO composite material according to claim 2, characterized in that: In step (1), the concentration of aqueous ammonia is 25%wt, the mixing ratio of aqueous ammonia to anhydrous ethanol is 1:10, and the stirring time is not less than 10 minutes; the concentration of resorcinol dissolved in ultrapure water is 0.3-0.4M, and the stirring time is not less than 10 minutes.

4. The method for preparing the spherical C@MnO composite material according to claim 2, characterized in that: In step (2), the concentration of the formaldehyde solution is 30-40%wt, and the volume ratio of the formaldehyde solution to solution A and solution B is 1mL:77mL:10mL.

5. The method for preparing the spherical C@MnO composite material according to claim 2 or 4, characterized in that: In step (2), the reaction time for synthesizing the RF spherical material is 12-14 hours, and the reaction temperature is 25-30°C.

6. The method for preparing the spherical C@MnO composite material according to claim 2, characterized in that: In step (3), the concentration of the potassium permanganate solution is 0.05-0.08 M, and the amount ratio of the RF spherical material to the potassium permanganate solution is 100 mg:10 mL; the reaction time is 6 h, and the reaction temperature is 25-30° C.

7. The method for preparing the spherical C@MnO composite material according to claim 2, characterized in that: In step (4), the temperature of high temperature heat treatment is 400-600°C, the heating rate is 2-5°C / min, and the heat treatment time is 6-8h.

8. Use of the spherical C@MnO composite material as claimed in claim 1 or the spherical C@MnO composite material prepared by the method as claimed in claim 2 in the modification of the separator of a lithium-sulfur battery.